The ‘inauthentic’ naturalized citizens: the case of foreign sports athletes in elite sports - Woo, Shawn (2017)
This paper aims to study how a Singaporean identity can be constructed via the use of sports, and how the use of the Foreign Sports Talent scheme has impacted national identity. The use of the FST scheme was to discuss the intersectionalities of both immigration and national identity and sports. We then analyze how opinions between members of the public differ from national elite athletes themselves, a group that is directly affected by the introduction of the scheme. Our findings showed that factors like age and embeddedness in the sporting set-up were significant factors in affecting their perceptions of the effectiveness of the FST scheme and the acceptance of the foreign athletes themselves.